2015
DOI: 10.1002/hed.24298
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for locoregional relapse after transoral robotic surgery for human papillomavirus–related oropharyngeal squamous cell carcinoma

Abstract: Traditional indications for adjuvant RT or CRT were associated with high risk of locoregional relapse in HPV-positive patients treated with TORS alone. © 2015 Wiley Periodicals, Inc. Head Neck 38: E1674-E1679, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…Second, the selection of candidates for TORS as a first-line treatment has predominantly been based on clinical T-staging to date. 2,5,[27][28][29][30] However, because the status of the constrictor muscle or parapharyngeal fat in HPV-positive tonsillar SCC is not currently applied in the AJCC staging 21 or NCCN guidelines, 22 there is risk of selecting improper patients for surgery who are predicted to have an insecure margin. We hope that our study result can be a motive for future prospective clinical trials to verify the interrelation between the MR imaging score and clinical staging.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the selection of candidates for TORS as a first-line treatment has predominantly been based on clinical T-staging to date. 2,5,[27][28][29][30] However, because the status of the constrictor muscle or parapharyngeal fat in HPV-positive tonsillar SCC is not currently applied in the AJCC staging 21 or NCCN guidelines, 22 there is risk of selecting improper patients for surgery who are predicted to have an insecure margin. We hope that our study result can be a motive for future prospective clinical trials to verify the interrelation between the MR imaging score and clinical staging.…”
Section: Discussionmentioning
confidence: 99%
“…Weinstein et al reported 30 patients undergoing transoral surgery and neck dissection alone with local control of 97% and regional control of 90%. Radiotherapy has been shown to decrease the risk of recurrence after surgical therapy in the setting of high‐risk recurrence features, such as multiple positive nodes and ECS . In the absence of these features, the risk of recurrence after neck dissection is <10%.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy has been shown to decrease the risk of recurrence after surgical therapy in the setting of high-risk recurrence features, such as multiple positive nodes and ECS. 25,26 In the absence of these features, the risk of recurrence after neck dissection is <10%. In our series, the overall incidence of local or regional recurrence was 8% at 5 years, and although the risk was increased in the surgery alone group (recall that many patients had refused adjuvant therapy), the 3-year local recurrence rate in this group was still <3%.…”
Section: Discussionmentioning
confidence: 99%
“…Human papillomavirus (HPV)‐related, p16‐positive oropharyngeal squamous cell carcinoma (OPSCC) has been shown as an unique disease entity with improved prognosis compared to p16‐negative OPSCC . The traditional prognosticators for p16‐negative OPSCC are shown to be less impactful in p16‐positive OPSCC due to its inherent favorable biology and treatment responsivess . Minimally invasive techniques using transoral laser microsurgery (TLM) and transoral robotic surgery (TORS) are commonly employed for the primary treatment of OPSCC .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The traditional prognosticators for p16-negative OPSCC are shown to be less impactful in p16-positive OPSCC due to its inherent favorable biology and treatment responsivess. [4][5][6][7][8][9] Minimally invasive techniques using transoral laser microsurgery (TLM) and transoral robotic surgery (TORS) are commonly employed for the primary treatment of OPSCC. [10][11][12][13][14][15][16] Favorable oncologic and functional outcomes with reduced treatment toxicity in p16-positive OPSCC are reported with these minimally invasive techniques in the short term.…”
Section: Introductionmentioning
confidence: 99%